Comparative study on the expression of Pax3, Rad51 and VEGF-C in esophageal gastric junction adenocarcinoma and distal gastric adenocarcinoma: Differential Expression of Pax3, Rad51, and VEGF-C in Gastric Cancers - Pan, Qiang; Liu, Xiangyang; Xu, Chen; Yu, Chengyuan (Cellular and Molecular Biology, 2024)
The purpose of this study was to explore the differential expression of Pax3, Rad51 and VEGF-C in esophageal gastric junction adenocarcinoma and distal gastric adenocarcinoma and their relationship with cancer occurrence and development. 57 patients with gastric cancer were included and divided into esophageal gastric junction adenocarcinoma group (n=28) and distal gastric adenocarcinoma group (n=29). The positive expressions of Pax3, Rad51 and VEGF-C in the control group were lower than those in the esophageal gastric junction adenocarcinoma group and distal gastric adenocarcinoma group respectively (P<0.05). In esophageal gastric junction adenocarcinoma with low differentiation, positive expressions of Pax3, Rad51, and VEGF-C surpassed those in high/medium differentiation (P<0.05). Serosa-infiltrated cases exhibited higher Pax3 and Rad51 expressions compared to non-infiltrated cases (P<0.05). Rad51 and VEGF-C positivity were notably elevated in cases with lymph node metastasis compared to those without (P<0.05). Distal gastric adenocarcinoma displayed higher VEGF expression than middle/low differentiated adenocarcinomas. Rad51 expression was significantly higher in women than in men (P<0.05). The positive rates of Pax3, Rad51, and VEGF-C were markedly increased in esophageal gastric junction adenocarcinoma and distal gastric adenocarcinoma compared to normal gastric tissue, and these were associated with the degree of differentiation, depth of invasion, and lymph node metastasis in patients. Particularly, Rad51 exhibited a positive correlation with cancer cell differentiation, invasion depth, and lymph node metastasis in cancer tissue.